SIFAT POLIMER DAN KEMAMPUAN TERBIODEGRADASI BLEND BIODEGRADABLE POLYMER POLI (L-ASAM LAKTAT) (PLLA) - Johnner P Sitompul; Rizki Insyani; Hyung Woo Lee (Reaktor, 2014)
Poly(D,L-lactic acid) (PDLLA) and poly(ethylene glycol) (PEG) was used to modify mechanical and biodegradability properties of poly(L-lactic acid) (PLLA) through solution blending method using solvent mixture of dichloromethane-ethanol. Polymer samples were then characterized using FTIR, DSC, UTM, and enzymatic degradation test. FTIR spectrum of pure PLLA showed specific IR absorption peaks at wavenumber of 3504 cm-1 (-OH), 1757 cm-1 (-C=O), and 1381 cm-1 (-CH3 symmetric). Further, polymer blend samples showed absorption peak shifts at 1755 cm-1 and 1382 cm-1 for PLLA/PDLLA due to stereocomplex interaction and at 3429 cm-1 due to hydrogen bond interaction. DSC results showed that there was melting temperature depression for all polymer blend samples compared to pure PLLA with increasing of either PDLLA or PEG composition. In PLLA/PDLLA, two melting points were discovered because of homocrystallite and stereocomplex phase formation. While PLLA/PEG samples showed increasing crystallinity to 69% at 20%-wt PEG composition. Mechanical analysis showed that 10%-wt of PDLLA addition in PLLA produced better mechanical performance than pure PLLA while 20%-wt of PEG addition showed highest elongation at break with the value of 89%. Polymer blend samples were degradable during enzymatic degradation test represented by percent weight loss with maximum value of 21% for PLLA/PEG sample. Keywords: polymer properties, solution-blending, Poly(lactic acid), polymer blend, enzymatic degradation